A Prodromal Brain‐Clinical Pattern of Cognition in Synucleinopathies. Issue 2 (7th December 2020) - Rahayel, Shady; Postuma, Ronald B.; Montplaisir, Jacques; Mišić, Bratislav; Tremblay, Christina; Vo, Andrew; Lewis, Simon; Matar, Elie; Ehgoetz Martens, Kaylena; Blanc, Frédéric; Yao, Chun; Carrier, Julie; et al.
Abstract : Objective: Isolated (or idiopathic) rapid eye movement sleep behavior disorder (iRBD) is associated with dementia with Lewy bodies (DLB) and Parkinson's disease (PD). Biomarkers are lacking to predict conversion to a dementia or a motor‐first phenotype. Here, we aimed at identifying a brain‐clinical signature that predicts dementia in iRBD. Methods: A brain‐clinical signature was identified in 48 patients with polysomnography‐confirmed iRBD using partial least squares between brain deformation and 27 clinical variables. The resulting variable was applied to 78 patients with iRBD followed longitudinally to predict conversion to a synucleinopathy, specifically DLB. The deformation scores from patients with iRBD were compared with 207 patients with PD, DLB, or prodromal DLB to assess if scores were higher in DLB compared to PD. Results: One latent variable explained 31% of the brain‐clinical covariance in iRBD, combining cortical and subcortical deformation and subarachnoid/ventricular expansion to cognitive and motor variables. The deformation score of this signature predicted conversion to a synucleinopathy in iRBD ( p = 0.036, odds ratio [OR] = 2.249; 95% confidence interval [CI] = 1.053–4.803), specifically to DLB (OR = 4.754; 95% CI = 1.283–17.618, p = 0.020) and not PD ( p = 0.286). Patients with iRBD who developed dementia had scores similar to clinical and prodromal patients with DLB but higher scores compared with patients with PD. The deformation score also predicted cognitive performance over 1, 2, and 4 years in patients with PD. Interpretation: We identified a brain‐clinical signature that predicts conversion in iRBD to more severe/dementing forms of synucleinopathy. This pattern may serve as a new biomarker to optimize patient care, target risk reduction strategies, and administer neuroprotective trials. ANN NEUROL 2021;89:341–357